Assessing Bermuda's parliament against the CPA benchmarks (2014)
Reports on the conduct of an examination of Bermuda's legislature to ensure that it me the standards detailed in the Commonwealth Parliamentary Association Benchmarks for Democratic Legislatures.
Keywords: PARLIAMENT